Marker-free co-selection for successive rounds of prime editing in human cells - Sébastien Levesque; Diana Mayorga; Jean-Philippe Fiset; Claudia Goupil; Alexis Duringer; Andréanne Loiselle; Eva Bouchard; Daniel Agudelo; Yannick Doyon (Nature Communications, 2022)
Prime editing enables the introduction of precise point mutations, small insertions, or short deletions without requiring donor DNA templates. Here the authors develop a co-selection strategy to facilitate prime editing in human cells and provide design principles to prevent the formation of undesired editing byproducts at the target site.